Indicadores de alfabetização científica identificados nas atividades experimentais propostas em livros didáticos de ciências nos anos iniciais - Polydoro, Agda Melania (2020)
This research addresses the Scientific Literacy (CA) in the Early Years of Elementary School, according to the indicators proposed by Sasseron and Carvalho. It was verified whether the experimental activities in the textbooks for the Early Years of Elementary School contained CA indicators and which ones, even for a more contextualized and undisciplinary learning of the mother tongue. The research is justified by the fact that the textbook is still the main didactic resource used by teachers in the classroom. The Teacher's Book of the Learning Together Science collection, approved by the National Textbook Program (PNLD / 2019) for the Early Years of Elementary School (1st to 5th grade), was analyzed in order to verify if and which indicators of CA are present in the experimental activities proposed in this collection; signal limits and possibilities for the use of the collection in the teaching-learning process. This is a qualitative research, such as Document Analysis. After analyzing the collection it was found that the CA indicators, present in the experimental activities, ensure a better understanding of the theoretical content and the junction of the conceptual aspect with reality, contribute to the progressive advancement of students' scientific knowledge, besides offering a dialogical environment, conducive to building challenges, raising hypotheses, developing skills such as argumentation and critical thinking, facilitating the use of the orthographic system from the CA.